Cotton-based wearable PEDOT:PSS electronic sensor for detecting acetone vapor. (4th December 2017) - Zhang, Yalei; Cui, Yue
Abstract: Developing a wearable sensor to detect acetone vapor has great potential for healthcare applications. PEDOT:PSS has recently attracted great interest as a highly conductive polymeric electronic material that can be easily processed. Cotton thread is one of the basic materials used in producing garments. Here, we show for the first time the development of a wearable PEDOT:PSS sensor based on cotton thread. The sensor provides rapid and highly sensitive detection of acetone vapor. We anticipate that these results could open significant opportunities for fundamental studies of wearable electronic sensors, as well as a variety of real-time and on-site applications in fields including medical diagnosis, environmental monitoring, and defense.